Antioxidant-based Evaluation of Seed Extracts of Two Maize Varieties for Medicinal Purpose: Scavenging Mechanism in Seed Extract of Maize Varieties - Ahmad, Anus; Ahmed, Usman; Ahmad, Nisar; Muhammad, Asim (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2016)
The aim of this study was to explore the medicinal value of seeds of two maize varieties obtained from Cereal Crop Research Institute, Pirsabak, Nowshera, Pakistan. The antioxidant system was evaluated in the methanolic seed extract using DDPH, ABTS, Phosphomolybdate and hydrogen peroxide scavenging activities. Here, we showed that both Azam and Iqbal varieties exhibited high scavenging activities at minimum and maximum extract concentrations against free radicals at a level comparable to ascorbic acid (standard). DPPH was the only free radical that was scavenged 50% less in comparison to standard whereas for ABTS, hydrogen peroxide and phosphomolybdate both varieties respond more or less the same as for ascorbic acid. Moreover, compared to Azam, Iqbal variety showed better antioxidant mechanism at 0.75 mg mL-1 and 1.5 mg mL-1 extract concentration against ABTS and phosphomolybdate. These high scavenging activities of the methanolic extract indicate that seeds of both varieties possess good antioxidant system in removing of free radicals and thus can be a potent medicinal plant for the treatment of oxidative stress and can be considered as good health supplement.